2019
DOI: 10.1108/cg-04-2018-0138
|View full text |Cite
|
Sign up to set email alerts
|

Board nationality and educational background diversity and corporate social performance

Abstract: Purpose This paper aims to examine the relationship between the nationality and educational background diversity of directors serving on corporate boards and the firms’ corporate social performance (CSP). Design/methodology/approach This study measures nationality diversity by directors’ national citizenship and measures educational background diversity by countries from which they earned their undergraduate and post undergraduate degrees. It measures firms’ CSP using the MSCI ESG ratings. The study uses bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
141
5
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(169 citation statements)
references
References 49 publications
17
141
5
6
Order By: Relevance
“…Compared to other articles on board of directors' effectiveness, many independent and dependent variables were used to answer the question of the way diversity affects innovativeness in highly ranked companies compared to bioeconomy companies. We argue that because diversity attributes combined with education are considered some of the fundamental aspects that influence the assortment of human ideas, opinions and team dynamics, the greater the diversity in these observed characteristics, the higher the likelihood for diversity of thought (Ely et al, 2012;Rabl and Triana, 2013;Harjoto et al, 2019). Gender diversity was the only diversity-related attribute examined that did not differ between the bioeconomy and top ten most innovative companies.…”
Section: Bioeconomymentioning
confidence: 94%
“…Compared to other articles on board of directors' effectiveness, many independent and dependent variables were used to answer the question of the way diversity affects innovativeness in highly ranked companies compared to bioeconomy companies. We argue that because diversity attributes combined with education are considered some of the fundamental aspects that influence the assortment of human ideas, opinions and team dynamics, the greater the diversity in these observed characteristics, the higher the likelihood for diversity of thought (Ely et al, 2012;Rabl and Triana, 2013;Harjoto et al, 2019). Gender diversity was the only diversity-related attribute examined that did not differ between the bioeconomy and top ten most innovative companies.…”
Section: Bioeconomymentioning
confidence: 94%
“…Extant literature has found that corporate governance effectiveness, monitoring, and corporate decision-making are influenced by board of directors' informal professional and social networks (Alipour et al, 2019;Cohen, Frazzini, and Malloy, 2008;Harjoto, Laksmana and Yang, 2019;Hochberg, Ljungqvist, and Lu, 2007;Kuhnen, 2009;Seidel, Polzer, and Stewart, 2000). For instance, Cohen et al (2010) find that sell-side analysts who have educational connections with companies' board of directors tend to perform better in their stock recommendations.…”
Section: Board Network and Corporate Social Performancementioning
confidence: 99%
“…They found a positive relationship between the knowledge and experience of board and firm performance. More recent investigations, including Harjoto et al (2019) examine the relationship between the nationality and educational background diversity of directors serving on corporate boards and the firms' corporate social performance (CSP). They find that board nationality diversity and educational background diversity are positively associated with CSP.…”
Section: The Board's Financial Expertisementioning
confidence: 99%